Multidisciplinary Service Utilization Pattern by Advanced Head and Neck Cancer Patients: A Single Institution Study. (18th October 2012) - Junn, Jacqueline C.; Kim, Irene A.; Zahurak, Marianna L.; Tan, Marietta; Fan, Katherine Y.; Lake, Spencer T.; Zaboli, David; Messing, Barbara P.; Ulmer, Karen; Harrer, Karen B.; Gold, Dorothy; Ryniak, Keri L.; et al.
Abstract : Purpose . To analyze the patterns and associations of adjunctive service visits by head and neck cancer patients receiving primary, concurrent chemoradiation therapy. Methods . Retrospective chart review of patients receiving adjunctive support during a uniform chemoradiation regimen for stages III-IV head and neck squamous cell carcinoma. Univariate and multivariate models for each outcome were obtained from simple and multivariate linear regression analyses. Results . Fifty-two consecutive patients were assessed. Female gender, single marital status, and nonprivate insurance were factors associated with an increased number of social work visits. In a multivariate analysis, female gender and marital status were related to increased social work services. Female gender and stage IV disease were significant for increased nursing visits. In a multivariate analysis for nursing visits, living greater than 20 miles between home and hospital was a negative predictive factor. Conclusion . Treatment of advanced stage head and neck cancer with concurrent chemoradiation warrants a multidisciplinary approach. Female gender, single marital status, and stage IV disease were correlated with increased utilization of social work and nursing services. Distance over 20 miles from the center was a negative factor. This information may help guide the treatment team to allocate resources for the comprehensive care of patients.